2016
DOI: 10.1001/jamasurg.2016.1239
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Population-Level Spatial Access to Essential Surgical Care in Ghana Using Availability of Bellwether Procedures

Abstract: IMPORTANCE Conditions that can be treated by surgery comprise more than 16% of the global disease burden. However, 5 billion people do not have access to essential surgical care. An estimated 90% of the 87 million disability-adjusted life-years incurred by surgical conditions could be averted by providing access to timely and safe surgery in low-income and middle-income countries. Population-level spatial access to essential surgery in Ghana is not known. OBJECTIVES To assess the performance of bellwether pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…We generated a travel impedance surface by assigning travel speeds of 100 km/h to primary roads, 50 km/h to secondary roads, and 30 km/h to tertiary roads on the basis of previous studies. 18 , 19 The model does not give any measures of uncertainty; and for sensitivity analysis, we varied the motorised speeds by more or less than 20% of the original speeds 19 , 20 to define an upper and lower bound of uncertainty around travel speeds. We assigned the other non-road raster cells with speeds of 5 km/h, assuming patients could walk, were carried, or were transported with use of other means to the nearest road before obtaining motorised travel.…”
Section: Methodsmentioning
confidence: 99%
“…We generated a travel impedance surface by assigning travel speeds of 100 km/h to primary roads, 50 km/h to secondary roads, and 30 km/h to tertiary roads on the basis of previous studies. 18 , 19 The model does not give any measures of uncertainty; and for sensitivity analysis, we varied the motorised speeds by more or less than 20% of the original speeds 19 , 20 to define an upper and lower bound of uncertainty around travel speeds. We assigned the other non-road raster cells with speeds of 5 km/h, assuming patients could walk, were carried, or were transported with use of other means to the nearest road before obtaining motorised travel.…”
Section: Methodsmentioning
confidence: 99%
“…A macro-level study of nine countries showed that the proportion of a country’s population living within a 2-hour drive of essential surgical services varied from 17% (Somaliland) to 84% (Pakistan). 11 Studies in Zambia 12 and Ghana 13 have attempted to use more granular mapping techniques to estimate countrywide access to surgical services and inform health systems planning. Of note, the Ghana study was able to identify five health facilities which were already providing some surgical services and had large catchment areas, making them ideal ‘targets’ for the expansion of their surgical services to increase timely access to care.…”
Section: Introductionmentioning
confidence: 99%
“…By reporting the six Global Health indicators for APH and Milne Bay Province, our team have developed a methodology that can be followed by other hospitals in PNG and the Pacific. 10 The study on Bellwether access in our region was not based on estimated times from geo-spatial mapping 16 but rather by real journey times and only patients who reached hospital were included. However, our study did measure the real delays and identified that lack of transport has a major and real impact, regardless of distances by road or overseas.…”
Section: Discussionmentioning
confidence: 99%